The β-Lactamase Gene Profile and a Plasmid-Carrying Multiple Heavy Metal Resistance Genes of Enterobacter cloacae. (20th December 2018) - Wu, Chongyang; Lin, Chaoqin; Zhu, Xinyi; Liu, Hongmao; Zhou, Wangxiao; Lu, Junwan; Zhu, Licheng; Bao, Qiyu; Cheng, Cong; Hu, Yunliang
Abstract : In this work, by high-throughput sequencing, antibiotic resistance genes, including class A ( bla CTX-M, bla Z, bla TEM, bla VEB, bla KLUC, and bla SFO ), class C ( bla SHV, bla DHA, bla MIR, bla AZECL-29, and bla ACT ), and class D ( bla OXA ) β -lactamase genes, were identified among the pooled genomic DNA from 212 clinical Enterobacter cloacae isolates. Six bla MIR -positive E. cloacae strains were identified, and pulsed-field gel electrophoresis (PFGE) showed that these strains were not clonally related. The complete genome of the bla MIR - positive strain (Y546) consisted of both a chromosome (4.78 Mb) and a large plasmid pY546 (208.74 kb). The extended-spectrum β -lactamases (ESBLs) ( bla SHV-12 and bla CTX-M-9a ) and AmpC ( bla MIR ) were encoded on the chromosome, and the pY546 plasmid contained several clusters of genes conferring resistance to metals, such as copper ( pco ), arsenic ( ars ), tellurite ( ter ), and tetrathionate ( ttr ), and genes encoding many divalent cation transporter proteins. The comparative genomic analyses of the whole plasmid sequence and of the heavy metal resistance gene-encoding regions revealed that the plasmid sequences of Klebsiella pneumoniae (such as pKPN-332, pKPN-3967, and pKPN-262) shared the highest similarity with those of pY546. It may be concluded that a variety of β -lactamase genes present in E. cloacae which confer resistance to β -lactam antibiotics and the emergence of plasmids carrying heavy metal resistance genes in clinical isolates are alarming and need further surveillance.